Prevalence of Major Depressive Disorder Among Adults in China: A Systematic Review and Meta-Analysis - Zhao, Yan-Jie; Jin, Yu; Rao, Wen-Wang; Zhang, Qing-E; Zhang, Ling; Jackson, Todd; Su, Zhao-Hui; Xiang, Mi; Yuan, Zhen; Xiang, Yu-Tao (Frontiers in Psychiatry, 2021)
Background: Prevalence estimates of major depressive disorder (MDD) among adults in China have varied widely between studies. In this systematic review and meta-analysis, the overall prevalence of MDD in the Chinese population was estimated from published epidemiological studies and potential moderators that account for variability is estimates were assessed. Methods: A systematic literature search was conducted in PubMed, EMBASE, Web of Science, PsycINFO, China National Knowledge Internet (CNKI) and WanFang databases to identify relevant studies. Data analyses were conducted using the Comprehensive Meta-Analysis Version 2.0. Results: Forty studies involving 1,024,087 subjects were included. The pooled point, 12-month and lifetime prevalence rates of MDD in China were 1.1% (95% CI: 0.9%-1.4%), 1.6% (95% CI: 1.0%-2.5%) and 1.8% (95% CI: 1.5%-2.2%), respectively. Subgroup and meta-regression analyses revealed gender, marital status and survey year as significant moderators with higher MDD rates observed in divorced or widowed subgroups, women, and more recently published studies. Conclusion: The overall prevalence of MDD in the Chinese population appears to be lower than that of most countries but rates have been increasing over time and are elevated in particular demographic subgroups. In order to reduce negative health outcomes of MDD, effective preventive measures, early identification and timely treatments should be offered to those in need.